2022
DOI: 10.3389/frwa.2022.722269
|View full text |Cite
|
Sign up to set email alerts
|

Low Cost, Recyclable and Magnetic Moringa Oleifera Leaves for Chromium(VI) Removal From Water

Abstract: Chromium(VI) a heavy metal by nature, is one of the most toxic metals in the environment. We recently reported functionalized Moringa Oleifera (FMO) leaves as a low cost and efficient adsorbent for the removal of Cr(VI) and bacterial from water, as a continuation, we report the incorporation of magnetic nanoparticles (Fe3O4) with previously studied FMO for Cr(VI) removal from aqueous solution. Iron oxide due to its magnetic properties has been shown to assist in the recovery of its adsorbents. In this study, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…While these biosorbents are cheap, efficient, and readily available, their metal sequestration capacity is poor. Techniques like cross-linking, chemical modification, and activation can increase this capacity for highly efficient adsorption [19,20]. In fact, Anastopoulos et al [21] reported that agro-industrial waste without prior treatment could cause problems with chemical and biological oxygen demand, resulting in environmental pollution and harmful effects on human and animal health [22].…”
Section: Introductionmentioning
confidence: 99%
“…While these biosorbents are cheap, efficient, and readily available, their metal sequestration capacity is poor. Techniques like cross-linking, chemical modification, and activation can increase this capacity for highly efficient adsorption [19,20]. In fact, Anastopoulos et al [21] reported that agro-industrial waste without prior treatment could cause problems with chemical and biological oxygen demand, resulting in environmental pollution and harmful effects on human and animal health [22].…”
Section: Introductionmentioning
confidence: 99%
“…Another popular disinfection or removal technique is chlorination, which involves chemical reactions between organic pollutants and chlorine to produce some harmful toxic byproducts such as trihalomethanes (THMs) and haloacetic acid (Haa) . On the other hand, electrochemical advanced processes (EAOPs), photocatalysis, and piezocatalysis have been reported to be the most suitable methods for the degradation of recalcitrant organics since they do not generate any secondary pollution. , These methods use generated reactive oxygen species such as hydroxyl, superoxide, and hydrogen peroxide radicals to break down organic pollutants into less harmful byproducts such as water (H 2 O) and carbon dioxide (CO 2 ) . However, EAOPs require an external electric supply; thus, high energy consumption is used .…”
Section: Introductionmentioning
confidence: 99%